Philippine Cultural Studies in Focus Localizing the Global, Globalizing the Local - Fernandez, Steven Patrick C. (2013)
Culture can only be understood through overarching disciplines. One discipline cannot be fragmented from the other. Like the nation, culture is composed of various parts, each will own its synthetized relationship with the other parts producing causal relationships acting on all the others.

Each part seeks their own functions in confluence with the others and once set, these functions in a reflexive way produce the form society survives in. The connected-ness of all these parts forms society.It is what we see. We sense Culture through forms that articulate values, ideals, the social relationships allowed, hierarchy, the manifestation of Order, and the consciousness that a society nurtures. These are its creative expressions, the Arts. These expressions are the marks of culture, a people's identity, which in reflexive ways ensure its integrity. Yet the foundations of our identity, our social relationships, and our lifestyles are threatened by a deluge that comes with modernity. This deluge called Globalization is a threat we can do little about. It is imminent. It will drown our culture in due time to produce new states of consciousness, expressed with new forms manifesting new acquired values. We can only slow down its effects countering the disintegration of our nation-state' by buffering it with knowledge sourced from our own indigenous wells.
Keywords: Globalization -- Social aspects